ANALISIS TINGKAT KEPUASAN PELANGGAN ATAS KUALITAS PELAYANAN DAN HARGA PADA PO. SINDORO SATRIAMAS SEMARANG - M Ibnu Khaldun; Apriatni Endang Prihatini (Universitas Diponegoro, 2016)
The research was motivated by of the many various alternative options for transportation services, especially land transportation. However, bus still be alternative options for most of Indonesian people as a means of drive. The purpose of this research was to determine the customer’s satisfaction level on the service quality and the price of PO. Sindoro Satriamas’s customer. The type of research used was descriptive analysis research. The population were all passengers of PO. Sindoro Satriamas with sample of as many as 100 respondents with sampling technique used was purposive sampling and accidental sampling. The analysis of data used in this research was the Importance and Performance Analysis. Based on the Importance and Performance Analysis, then the conclusion that the average total for the service quality was 82,84% included in the satisfied category and the average total for the price was 80,17% included in the satisfied category too. Suggestions can be submitted to the company is improving the performance of quality service and price optimally so that created the suitability between the expectations of customers with the company's performance.